Dietary Fiber Intake Is Related to Skeletal Muscle Mass, Body Fat Mass, and Muscle-to-Fat Ratio Among People With Type 2 Diabetes: A Cross-Sectional Study - Takahashi, Fuyuko; Hashimoto, Yoshitaka; Kaji, Ayumi; Sakai, Ryosuke; Kawate, Yuka; Okamura, Takuro; Okada, Hiroshi; Kitagawa, Noriyuki; Nakanishi, Naoko; Majima, Saori; Osaka, Takafumi; Senmaru, Takafumi; et al. (Frontiers in Nutrition, 2022)
Objectives: To investigate the relationship between dietary fiber intake and skeletal muscle mass, body fat mass, and muscle-to-fat ratio (MFR) among men and women with type 2 diabetes (T2D). Methods: This cross-sectional study involved 260 men and 200 women with T2D. Percent skeletal muscle mass (%) or percent body fat mass (%) was calculated as (appendicular muscle mass [kg] or body fat mass [kg] / body weight [kg]) × 100. MFR was calculated as appendicular muscle mass divided by body fat mass. Information about dietary fiber intake (g/day) was obtained from a brief-type self-administered diet history questionnaire. Results: Dietary fiber intake was correlated with percent body fat mass (r = −0.163, p = 0.021), percent skeletal muscle mass (r = 0.176, p = 0.013), and MFR (r = 0.157, p = 0.026) in women. However, dietary fiber intake was not correlated with percent body fat mass (r = −0.100, p = 0.108), percent skeletal muscle mass (r = 0.055, p = 0.376), and MFR (r = 0.065, p = 0.295) in men. After adjusting for covariates, dietary fiber intake was correlated with percent body fat mass (β = −0.229, p = 0.009), percent skeletal muscle mass (β = −0.364, p <0.001), and MFR (β = −0.245, p = 0.006) in women. Further, dietary fiber intake was related to percent skeletal muscle mass (β = 0.221, p = 0.008) and tended to be correlated with percent body fat mass (β = −0.148, p = 0.071) in men. Conclusion: Dietary fiber intake was correlated with skeletal muscle mass, body fat mass, and MFR among women with T2D.